Analysis of Clinical Features and Next-Generation Sequencing of 12 Tuberous Sclerosis Families in China - Wang, Xu; Wang, Wenda; Zhao, Yang; Wang, Zhan; Zhang, Yushi (Frontiers in Medicine, 2022)
Background: Tuberous sclerosis complex (TSC) is a rare autosomal dominant genetic disease with systemic organs involvement. Till now, only a few TSC families in China have been reported. Therefore, more data on the clinical and genetic features of TSC families are required. Materials and Methods: We retrospectively analyzed 12 TSC family probands and their family members. Next-generation sequencing has been applied to confirm the type of TSC mutation along with detailed physical examination Results: Twenty-seven patients in 12 TSC families were reported, including 12 male and 15 female patients, aged 8-67 years. Skin lesions were detected among all TSC patients, including 25 cases of facial angiofibromas, 18 cases of hypomelanotic macules, 15 cases of ungual fibromas, and 13 cases of shagreen patch. Other clinical features were also revealed: 14 cases of renal angiomyolipoma, 6 cases of subependymal nodules, and 3 case of lymphangioleiomyomatosis. All twenty-seven TSC patients were tested by next-generation sequencing. Totally, TSC2 mutations were reported in 19 cases (7 frameshift mutations, 10 nonsense mutations and 2 missense mutation), TSC1 mutations were reported in 4 cases (4 nonsense mutations) and 4 cases were genetically negative. The novel causal mutations (TSC2: c.208dup, c.1874C>G, c.1852del) identified in 3 families were first reported in TSC. Conclusion: Our findings expand the mutation spectrum of TSC patients in China. The clinical characteristics can vary among TSC patients with the same pathogenic mutation. The genetic results and summary of clinical features of 12 TSC families contributes to a more accurate diagnosis and further genetic counseling.